Assessing the suitability for urban stream rehabilitation in Fort Collins based on watershed, hydrologic, and benthic macroinvertebrate indicators - Roznowski, Steven K., author; Roesner, Larry A., advisor; Kondratieff, B. C. (Boris C.), committee member; Ramírez, Jorge A., committee member (Colorado State University. Libraries, 2010)
Development in urban areas generally increases the proportion of a watershed that is covered by impervious surfaces. This added impervious area causes both the quantity and peak rate of stormwater runoff to increase thereby altering the natural flow regime in receiving streams and causing changes in sediment transport. Such changes in hydrology and sediment load can adversely affect benthic macroinvertebrates residing in channel beds. This study assesses the degree to which watershed development has impacted urban streams in Fort Collins, Colorado and recommends areas for rehabilitation that are most likely to benefit from watershed or in-stream modification. Fort Collins has recently begun implementing best management practices (BMPs) to help control stormwater runoff from developed areas. Locations and coverage of BMPs along with other measures of urbanization are compared to available stream flow and shear stress data which are in-turn related to benthic macroinvertebrate indicators. By drawing comparisons between these parameters, the effectiveness of stormwater BMPs can be assessed. This allows for recommendations to be made which direct stream rehabilitation efforts in the City. The impacts of irrigation flows in the Fort Collins area were found to limit the effectiveness of BMPs. This irrigation influence made trends difficult to establish between benthic macroinvertebrate indicators and watershed characteristics. However, as evidenced by recent improvements in macroinvertebrate indicators at one location, the combination of BMPs and in-stream improvement can create habitat suitable for rich macroinvertebrate communities provided irrigation flows are controlled. Therefore, the locations with large portions of the watershed protected by water quality BMPs and relatively little irrigation impact are targeted as prime locations for in-stream rehabilitation. For areas with low levels of water quality control, it is suggested that water quality BMPs be added before in-stream rehabilitation is undertaken.
Department Head: Luis A. Garcia.
Keywords: Stream restoration -- Fort Collins -- Colorado; Restoration ecology -- Fort Collins -- Colorado